Teknologi Pendidikan Islam di Masa Pandemi - Unik Hanifah Salsabila; Hairunnisa; Adena Widopuspito; Muhammad Wildanul Haq; Muhamad Rizaludin As'ad (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2021)
The purpose of this study is to examine the importance of technological progress. One of these aspects is to provide innovation for civilization in the era of digitalization. The purpose of this study is to describe the position of Islamic learning technology during the pandemic. Aims to perfect humans with Islamic personalities, and understand the life sciences which include science, technology, and art, and always provide solutions to online learning problems in Islamic life. So that educational technology functions in the world of learning. Future learning will prioritize communication networks with technological developments that allow them to be connected so that they can be useful. Technology will improve the quality of learning if used wisely for education and training, has an important meaning in welfare in order to educate the nation's life. Educational technology can only be considered important, if discipline is applied. So that it can develop by conducting technological research carried out using the right approach and resulting in the development of a research paradigm.